(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
This study focuses on assessing the spectrophotometric accuracy of presumptive tests for detecting bloodstains on various substrates, a critical aspect of forensic science in violent crime scene investigations. Blood, a complex substance rich in proteins and enzymes, serves as vital evidence but can deteriorate, posing challenges during forensic analysis. This research aims to address these challenges by evaluating the sensitivity and persistence of bloodstains on surfaces such as glass, tile, wood, cardboard, and linen over time.Utilizing three presumptive tests Phenolphthalein, Benzidine, and Leucomalachite Green and confirmatory tests Teichmann and Takayama this study investigates the efficacy of these methods over a period of up to nine weeks. Samples were subjected to spectral analysis to determine absorbance and track changes in reactivity. Initial findings reveal strong positive reactions from all tests up to three weeks, indicating high sensitivity. However, Leucomalachite Green exhibited a notable decline in sensitivity beyond the initial period, reflecting its limitations in long-term detection scenarios. Conversely, Benzidine and Phenolphthalein tests demonstrated consistent performance over extended durations, particularly on non-porous surfaces like glass and tile, which also showed the highest mean absorbance values in the spectrophotometric analysis. The Takayama confirmatory